Immediate Effect of Needling at CV-12 (Zhongwan) Acupuncture Point on Blood Glucose Level in Patients with Type 2 Diabetes Mellitus: A Pilot Randomized Placebo-Controlled Trial - Ranjan Kumar; A. Mooventhan; Nandi Krishnamurthy Manjunath (Medical Association of Pharmacopuncture Institute, 2017)
Introduction: Diabetes mellitus is a major global health problem. Needling at CV-12 has reduced blood glucose level in diabetic rats. The aim of this study was to evaluate the effect of needling at CV-12 (Zhongwan) on blood glucose level in patients with type 2 diabetes mellitus (T2DM). Materials and Methods: Forty T2DM patients were recruited and randomized into either the acupuncture group or placebo control group. The participants in the acupuncture group were needled at CV-12 (4 cun above the center of the umbilicus), and those in the placebo control group were needled at a placebo point on the right side of the abdomen (1 cun beside the CV-12). For both groups, the needle was retained for 30 minutes. Assessments were performed prior to and after the intervention. Statistical analysis was performed using SPSS version 16. Results: There was a significant reduction in random blood glucose level in the acupuncture group compared to baseline. No such significant change was observed in the placebo control group. Conclusion: The result of this study suggests that 30 minutes of needling at CV-12 might be useful in reducing blood glucose level in patients with T2DM.